Essays on immigration policies - Keller, Nicolas (2016)
This thesis empirically investigates three different aspects of immigration policies in Germany. In Chapter 2, I analyze whether the economic assimilation of refugees differs from the assimilation of economic immigrants. To create and implement effective immigration policies, it is necessary to understand the heterogeneity of different immigration groups. As a large part of low-skilled immigrants in the OECD originates from asylum seekers and low-skilled immigrants are a main target of immigration policies, a deeper understanding of that group is of high relevance. Moreover, immigration via the asylum system will most likely present an important channel for immigration in the future, given events like the recent refugee crisis in the European Union. If immigration policy tries to improve the economic integration of refugees, the peculiarities of the group of refugees should be taken into account designing policy measures. Chapters 3 and 4 analyze the effects of a particular policy instrument, the acquisition of citizenship. Naturalization grants an immigrant the citizenship of the host country by giving the immigrant the equal rights as the native population. It is predominantly directed to immigrants who have spent several years in the host country and requires specific criteria to be met. The third chapter which is joint work with Christina Gathmann investigates the effect of citizenship acquisition on the economic integration of immigrants. Making use of a novel identification strategy which is based on two policy reforms, we identify the causal effect of citizenship on various economic outcomes. An earlier version of this paper was circulated in the IZA Working Paper series (Gathmann and Keller, 2014). The fourth paper which is joint work with Christina Gathmann and Ole Monscheuer broadens the scope on the effects of citizenship acquisition and analyzes the impact of naturalization on the social integration of immigrants. In particular, we investigate the effects of naturalization on fertility and marriage patterns of immigrants. Despite the primary interest in the labor market effects of immigration policies, these policies might also have significant impact on other dimensions of integration. Previous research has shown that attitudes of natives toward immigrants and immigration in general are not only shaped by their economic impacts (i.e., on wages and taxes), but also on social and cultural differences (e.g., Card et al., 2012; Dustmann and Preston, 2007). Thus, the effects of immigration policies on social integration outcomes are also highly relevant, especially for policy makers which are confined by the public perception of immigration in general.